FORMATION AND INCREASE OF EXPORT POTENTIAL IN THE CONDITIONS OF DEEPENING OF EUROPEAN INTEGRATION PROCESSES OF UKRAINE - Galaziuk, N.M. (The actual problems of regional economy development, 2020)
The development of globalization processes makes all countries dependent on world markets for capital, goods and services, as a result of which all countries receive both shocks and incentives for their economic development. Not surprisingly, the pace and nature of development of the vast majority of countries around the world today depend on the successes or failures in the development of foreign economic relations. Ukraine's current foreign economic policy is aimed at European integration and promotion of domestic products on the European market, but increasing export potential is possible by updating or modernizing production processes and adapting to international quality standards set by importing countries. In the structure of Ukrainian exports, we see the advantage of raw materials and products of lower processing. That is why today the problem of development and diversification of the country's export potential is becoming urgent, the success of which will be determined by the scale and effectiveness of Ukraine's participation in the international division of labor in the deepening globalization of the world economy. Ukraine must become a country with a free economy, which provides for the formation of a favorable business environment with low tax pressure, minimizing state intervention in economic decision-making. The components of openness, as a rule, include: liberalization of foreign trade, the establishment of clear links between domestic and foreign price and currency dynamics, the willingness of domestic producers to compete in world markets. In this article, the object of study is the process of formation and increase of export potential of Ukraine in the conditions of European integration transformations. The study used specific and general economic methods, namely, abstract-logical, statistical research, determination of absolute, relative quantities, time series, as well as the method of unity of historical and logical, analysis and synthesis and other scientific research methods.